FOSTERING COMMUNICATIVE COMPETENCE IN UNIVERSITY STUDENTS THROUGH COMMUNICATIVE LANGUAGE TEACHING ENVIRONMENT - Salomova Dilnoza Bozor qizi; Jumayeva Nilufar Xudoynazarovna; Toshtemirova Hafiza Abdigapparovna (World Scientific Research Journal, 2025)
Abstract: This study explores the development and implementation of a Communicative Language Teaching (CLT) environment aimed at enhancing the communicative competence of university students. Given the increasing importance of effective communication skills in a globalized world, the research outlines a framework that integrates interactive pedagogical approaches, real-life communication scenarios, and collaborative learning experiences. Through a mixed-methods approach, data were collected from student assessments, surveys, and classroom observations to evaluate the impact of the CLT environment on students’ language proficiency and confidence in using English in various contexts. The findings indicate a significant improvement in students’ ability to engage in meaningful interactions, with enhanced fluency, accuracy, and pragmatic skills. The study underscores the necessity of creating a supportive and immersive linguistic atmosphere that prioritizes student engagement and encourages active participation.